Relationship between Physical Activity Level and Physical Literacy in Iranian Ethnic Children: A Cross-Cultural Study - Majid Mohammadi; Sheikh Mahmoud; Davood Hoomanian; Hasan Gharayagh Zandi; Mehrzad Hamidi (پژوهش‌های کاربردی روانشناختی)
The purpose of this cross-cultural study was to investigate the relationship between the level of physical activity and physical literacy among Iranian children. Descriptive-correlation was implemented in the current investigation. The study population consisted of 270 students from the centers of Khuzestan, Lorestan, Kurdistan, Tehran, East Azarbaijan, and Sistan and Baluchestan provinces in 2021, with an age range of 8 to 12 years (135 males, 135 girls). Using the cluster sampling method, they participated in this investigation. Data was collected using the Canadian Physical Literacy Test-2 and the International Child and Adolescent Physical Activity Questionnaire. Additionally, SPSS version 23 software was employed to conduct Pearson’s correlation coefficient test and two-way multivariate analysis of variance for data analysis. The results showed a positive and significant relationship between physical literacy and physical activity (P=0.001). The results of the geographical regions analysis indicated that the participants residing in Khorramabad, Sanandaj, and Zahedan exhibited significantly higher levels of physical activity and physical literacy than those residing in Tehran, Ahvaz, and Tabriz (P=0.001). The results of the study on the place of residence indicated that the children residing in the village exhibited a higher level of physical activity and physical literacy. Physical literacy (p=0.001) and physical activity (p=0.001) were significantly improved by gender. Based on the research findings, it seems that the physical literacy of children is influenced by a variety of factors, including gender, geographical regions, place of residence, and socio-cultural aspects. This is why it is advised that physical education programs implement decentralized planning.